Infection of Aedes albopictus with chikungunya virus rectally administered by enema - Nuckols, John T.; Ziegler, Sarah A.; Huang, Yan-Jang Scott; McAuley, Alex J.; Vanlandingham, Dana L.; Klowden, Marc J.; Spratt, Heidi; Davey, Robert A.; Higgs, Stephen (My University, 2013)
Chikungunya virus (CHIKV) is an alphavirus transmitted by Aedes albopictus and Aedes aegypti mosquitoes in tropical areas of Africa, Asia, and the islands of the Indian Ocean. In 2007 and 2009, CHIKV was transmitted outside these tropical areas and caused geographically localized infections in people in Italy and France. To temporally and spatially characterize CHIKV infection of Ae. albopictus midguts, a comparison of viral distribution in mosquitoes infected per os or by enema was conducted. Ae. albopictus infected with CHIKV LR 5′ green fluorescent protein (GFP) at a titer 10[superscript 6.95] tissue culture infective dose[subscript 50] (TCID[subscript 50])/mL, were collected and analyzed for virus dissemination by visualizing GFP expression and titration up to 14 days post inoculation (dpi). Additionally, midguts were dissected from the mosquitoes and imaged by fluorescence microscopy for comparison of midgut infection patterns between orally- and enema-infected mosquitoes. When virus was delivered via enema, the anterior midgut appeared more readily infected by 3 dpi, with increased GFP presentation observed in this same location of the midgut at 7 and 14 dpi when compared to orally-infected mosquitoes. This work demonstrates that enema delivery of virus is a viable technique for use of mosquito infection. Enema injection of mosquitoes may be an alternative to intrathoracic inoculation because the enema delivery more closely models natural infection and neither compromises midgut integrity nor involves a wound that can induce immune responses. Furthermore, unlike intrathoracic delivery, the enema does not bypass midgut barriers to infect tissues artificially in the hemocoel of the mosquito.
Keywords: Chikungunya virus; Aedes albopictus; Aedes aegypti; Enema injection